PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS: Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2020 - Friyanto, Friyanto; Masrifah, Fa’issa Barokatin; Saifuddin, Saifuddin (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
There are several objectives in this study, including: To find out and analyze the effect of receivable turnover and inventory turnover partially on profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. And also to find out and analyze the effect of receivable turnover and inventory turnover simultaneously on profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sample in this study was the financial statements on 9 (Nine) food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020 which amounted to 45 financial statements selected using purposive sampling techniques. The data used is secondary data taken from www.idx.co.id data. This study uses quantitative methods with multiple regression analysis techniques assisted by using the SPSS (Statistical Product and Service Solution) application program version 20. The results of the first t test proved that the hypothesis partially had no effect on independent variables i.e. the variable turnover of receivables to profitability was not proven to be true. While the results of the second t test proved that the hypothesis partially affects independent variables, namely inventory turnover to profitability is proven to be true. And the results of regression analysis from the F test showed that simultaneously or together there was an influence between the variable turnover of receivables and inventory turnover affecting profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange